Effect of High-Intensity Atorvastatin on the Prevalence of No-Reflow Phenomenon in Patient Undergoing Primary PCI: A Cross-Sectional Study - Muhammad Shahab-Ud-Din Khalil, Muhammad Asghar Khan, Zeeshan Afzal, Salah Uddin, Abdul Latif (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: ST-segment elevation myocardial infarction (STEMI) is one of the most common heart problems worldwide. So far percutaneous coronary intervention (PCI) has proved to be the most successful method to restore blood flow after a STEMI attack. However, the breakdown of coronary plaques often results in a failed restoration of blood. The no-reflow phenomenon complicates the treatment and delays the patient’s recovery. Statins have helped reduce cholesterol levels in the blood and have thus been used during primary PCI to enhance the chance of blood reflow. Atorvastatin is a promising candidate drug that reported promising results. Objective: In this study, the effect of high-intensity Atorvastatin has been assessed in preventing the no-reflow phenomenon. Study Design: Cross-sectional study Study Setting: Department of interventional Cardiology Hayatabad Medical Complex, Peshawar from 10-06-2022 to 10-10-2022. Material and Methods: A sample size of 149 was collected using non-probability consecutive sampling and was examined using Chi-Square for independence via the SPSS program. Results: The patients had several comorbidities, with hypertension being the most common. Over half of the patients were given atorvastatin, and over 97% of patients received balloon and stent procedures. 15% of patients experienced a no-reflow phenomenon, while 85% had a successful primary PCI. High-intensity atorvastatin was found to significantly reduce the risk of no-reflow (p < 0.001). Conclusion: The statistical outcome revealed that loading atorvastatin during the primary percutaneous coronary intervention (PCI) significantly reduces the risk of a no-reflow phenomenon. Keywords: ST-segment elevation myocardial infarction (STEMI), Atorvastatin, primary percutaneous coronary intervention (PCI), No-reflow phenomenon